REPRODUCTIVE BIOLOGY OF ANCHOVIES (Encrasicltolina heterolobzs AND Encrasicholina devisi) FROM BACAN, MALUKU - Retno Andamari; David Milton (Indonesian Fisheries Research Journal, 1998)
The repoductive biology of the anchovies, Enerasicholina heterolobus and E. devisi at Bacan were compered with published data from other parts of their geographic range. Sampling was carried out in April.